Designing B2B brands : lessons from Deloitte and 195,000 brand managers - Martinez Onaindia, Carlos; Resnick, Brian , 1974- (Wiley, 2013)
"This comprehensive manual lays out the steps necessary for creating an iconic global identity. It uses the lessons and inside knowledge of Deloitte, the world's largest professional services organization, to help other business-to-business operations deliver a high-impact, value-added brand experience. This book will illustrate all the components of an integrated brand identity system, and how they can be crafted and implemented for optimal effect. Here, the speculative is replaced by the proven: a seamless framework for global brand success created and followed by an organization renowned for its consulting and advisory services. Features essential up-to-date strategies for keeping your brand fresh and enduring, addresses the role of designers; the marketing and communication function; human resources and talent teams; agencies and vendors; and more considers the impact of digital and social media, two massive forces requiring new thinking for B2B brands, incorporates best practices for emerging markets. With guidance that takes you on a clear, linear path toward achieving your brand objectives, this impressive single-source volume is the one book no business marketing professional should be without." -- Publisher's description